EDUKASI SEKS REMAJA SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL DAN PERILAKU SAKS MENYIMPANG PADA REMAJA SANTRI - Christianingsih, Siska; Abdul Fauzi; Satria Eureka Nurseskasatmata; Caturia Sasti Sulistyana; Wiwin Sulistyawati; Yudi Dwi Saputra (Universitas Kadiri, 2025)
Adolescence is a vulnerable period in which curiosity about sexuality often arises but is not always accompanied by accurate information, especially among students in Islamic boarding schools. This community service focused on providing son for students at Pondok Pesantren Nurul Islam Kencong Jember as an effort to prevent sexual violence and deviant sexual behavior. The objectives were to improve knowledge and awareness of reproductive health, strengthen skills in refusing unhealthy sexual behavior, and foster the courage to report incidents within a safe pesantren environment. The program employed a participatory approach through interactive lectures, educational videos, group discussions, and pre–posttests. The results showed a significant increase in knowledge, with participants in the “Good” category rising from 4% to 77%, while those in the “Poor” category decreased from 65% to 8%. These findings indicate that contextual and value-based sexuality education is effective and can be replicated in similar pesantren settings